2011
DOI: 10.1007/s00024-011-0331-1
|View full text |Cite
|
Sign up to set email alerts
|

Dew Formation and Chemistry Near a Motorway in Poland

Abstract: Abstract-In this study, the influence of traffic intensity on dew formation efficiency and chemistry is presented. The measurements were conducted near the A4 motorway in SW Poland in almost flat land relief with intense agricultural activity. The dew/hoarfrost was collected by means of insulated plain passive radiative condensers at three sites: AN and AS located in the close vicinity of the motorway (30 m) on the opposite sides of the road, and AR, representing rural background conditions beyond the motorway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In other parts of the world, Gaiek et al [47], presented a systematic review on dew yield from plane radiative condensers in various field campaigns during 1993-2010. The overall outcome of these campaign results showed that the mean daily dew yield was in the range 0.06-0.20 L/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In other parts of the world, Gaiek et al [47], presented a systematic review on dew yield from plane radiative condensers in various field campaigns during 1993-2010. The overall outcome of these campaign results showed that the mean daily dew yield was in the range 0.06-0.20 L/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…However, one can say that dew water is the second largest load of water from the atmosphere to the Earth's surface in the investigated region (Polkowska et al, 2008;Tomaszkiewicz et al, 2015). In the European temperate continental zone (Dfb-Koppen climate classen), apart from the mountain and coastal regions, dew harvesting is unprofitable due to low efficiency, for example, 0.1 L/m 2 /day in the Netherlands (Jacobs et al, 2008), 0.15 L/m 2 /day in Sweden (Nilsson, 1996), and 0.1-0.4 mm in Poland (Galek et al, 2012;Muskała et al, 2015). Although dew water yield is limited and cannot exceed~1 mm/day (Beysens, 1995;Lekouch et al, 2010), it is strongly dependent on local conditions (Beysens, 2006;Galek et al, 2012;Rubio et al, 2008).…”
Section: Hydrological Situation Of Sampling Pointsmentioning
confidence: 99%
“…In the European temperate continental zone (Dfb-Koppen climate classen), apart from the mountain and coastal regions, dew harvesting is unprofitable due to low efficiency, for example, 0.1 L/m 2 /day in the Netherlands (Jacobs et al, 2008), 0.15 L/m 2 /day in Sweden (Nilsson, 1996), and 0.1-0.4 mm in Poland (Galek et al, 2012;Muskała et al, 2015). Although dew water yield is limited and cannot exceed~1 mm/day (Beysens, 1995;Lekouch et al, 2010), it is strongly dependent on local conditions (Beysens, 2006;Galek et al, 2012;Rubio et al, 2008). In dry periods between precipitation, dew is of considerable significance for ecosystems (especially in vegetation period); on the other hand, it is also hazardous due to its contribution to rotting of various naturals and propagation of epidemics (Agam & Berliner, 2006;Chen et al, 2013).…”
Section: Hydrological Situation Of Sampling Pointsmentioning
confidence: 99%
“…Polluting substances present in the atmospheric boundary layer are deposited during precipitation events. Beysens et al [6][7][8], Chiwa et al [9], Clus et al [10][11][12], and Galek et al [13] have measured precipitation levels and assessed chemical pollution content. Chemical attributes of deposited precipitation in India are presented in Muselli et al [14] and Sharan et al [15], for example.…”
Section: Introductionmentioning
confidence: 99%
“…Deposited precipitation, especially dew, is evaluated in some studies, usually as the by-product of analyzing deposited precipitation pollution. Examples of such studies include Beysens et al [7,8] and Muselli et al [16,17], for sampling areas in France; Muselli et al [14] and Mileta et al [18], for Croatia; Jacobs et al [19], for the central part of the Netherlands; Clus et al [12], for Tahiti; and Galek et al [13], for Poland.…”
Section: Introductionmentioning
confidence: 99%